Convergência para estados assintóticos em mapeamentos unidimensionais - Rando, Danilo Silva [UNESP] (2016)
In this work we investigate the behavior of the decay and relaxation to the equilibrium, especially at the bifurcation, for a family of one-dimensional discrete mappings, logistic- like. Our investigation consider three types of bifurcation: (i) transcritical; (ii) pitchfork and; (iii) period doubling. We discuss some scaling hypotheses leading to a scaling law involving three critical exponents. Near the fixed points, the dynamical variable varies very slowly. This property allows us to transform the equation of differences, hence natural from discrete mappings, into an ordinary differential equation (ODE). We solve such equation which furnishes the evolution towards the stationary state. Our numerical simulations confirm the theoretical results validating the above mentioned approximation.